PENENTUAN TRAJEKTORI KERETA DUBIN MELALUI KONTROL OPTIMUM - Tjahjana, Redemtus Heru (MATEMATIKA, 2012)
This paper addressed the control of a Dubinâ€™s vehicle. The Dubinâ€™s vehicle control design, using the Pontryagin Maximum Principle. The application of this principle, bring the matter to the Hamiltonian system with some partial equations excess conditions, while others do not have any conditions. The difference approach, which usedÂ in this paper to design of the control. This paper solve the problem by transforming the problem into the initial values problem, by finding the best approach to obtain the initial condition equations for some equations that do not have any conditions.